Suicidal “arterial cuts” with subtotal amputation of the left hand Suizidale „Pulsaderschnitte“ mit subtotaler Amputation der linken Hand - Janßen, K.; Jübner, M.; Rothschild, M. A.; Kamphausen, T. (Rechtsmedizin, 2018)
In the case of the death of a 76-year-old woman, the situation found at the scene including a distinctive bloodstain pattern and multiple sharp force trauma pointed to the question, whether the injuries were self-inflicted. Due to the results of the bloodstain pattern analysis, autopsy and toxicological analyses in combination with the police investigations, death by a third party could be excluded. Death was due to hemorrhagic shock caused by external bleeding through massive self-inflicted injuries. A special feature of the findings was the intensity of the cuts to the wrist leading to subtotal amputation of the hand.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Cut; Partial amputation; Sharp force; Suicide; Wrist